1) Let's prove this identity
Since tan (θ) = sin(θ)/cos((θ)
And cot((θ) = cos ((θ)/sin((θ)
2) Let's plug it into:
![\begin{gathered} \tan \text{ (}\theta)\cot \text{ (}\theta)\text{ =1} \\ (\sin (\theta))/(\cos (\theta))\cdot(\cos (\theta))/(\sin (\theta))=1 \\ 1=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n64f0ix76iop2bowr4ro0b7d4kdkqthg1u.png)
Simplifying (dividing) sin(θ) on the numerator, with sin (θ) on the denominator and similarly cos (θ) with cos(θ) we'll get to 1 over 1 time 1 over 1 = 1
Then 1=1